Methods for the conversion of biomass waste into value-added carbon nanomaterials: Recent progress and applications. (September 2022) - Tiwari, Santosh K.; Bystrzejewski, Michał; De Adhikari, Amrita; Huczko, Andrzej; Wang, Nannan
Abstract: Herein, we deliberate the recent progress and innovative modifications which were carried out during the last ten years as commonly employed methods for the conversion of biomass and related feedstocks into carbon nanosystems. Several highlighted methods are described in individual sections comprising: the type of nanomaterial processing, experimental conditions and factors affecting the yield and the characteristics of the final product. We have reconnoitred the applicability of specific feedstocks, advantages and drawbacks of the methods used for the conversion of biomass waste. A remarkable focus has been made to explore synthesis of graphene and graphene-like porous materials (with specific surface area greater than 1000 m 2  g −1 ) which were derived from biomass. Their prospective applications dedicated to smart materials and cutting-edge technologies are also described in each section. To maintain the readability and cover the previous stimulating works on carbon nanomaterials derived from biomass, the first section of this review recaps the present status of carbon nanomaterials derived from biomass and related precursors, chiefly for the application in electrochemical devices, catalysis, sensing, absorbent along with an ample bibliography for further reading. We believe that vast scientific data in this state-of-the-art, simple explanations with schematic diagrams and key future challenges will provide a solid platform to readers about the update in carbon materials derived from biomass waste.